ASUHAN KEPERAWATAN KELUARGA TAHAP PERKEMBANGAN LANSIA DENGAN INTERVENSI PENERAPAN KOMPRES HANGAT (TEPID WATER SPONGE) TERHADAP PENURUNAN NYERI ASAM URAT - Dini Trifani; Rina Puspita Sari; Hasan Basri (Yayasan Nusantara Hasana Berdikari, 2024)
The number of elderly people in Indonesia is 24.24% of the total population. The incidence of Gouty Arthritis is also relatively high in Indonesia. WHO revealed that the prevalence reached 81%, so Indonesia is ranked highest in sufferers of Gouty Arthritis in Asia. Based on data taken from practice reports at the Periuk Jaya Community Health Center, especially in Periuk Village, 17 people suffered from gout in July 2023. Management of gout can be done with pharmacological and non-pharmacological therapy. Pharmacologically, it collaborates with the administration of analgesics, according to research conducted, resulting in the conclusion that after carrying out the results, warm compresses are more effective in reducing pain in gout sufferers (Zahroh & Faiza, 2019). A warm compress is an easy and cheap measure, so it is hoped that it can overcome the pain complaints of elderly people with gout. This scientific paper is to describe the application of warm compresses to families experiencing gout to determine the effectiveness of warm compresses in reducing pain. The case study was carried out using warm compress therapy (Tepid Water Sponge) for 7 meetings lasting 10-15 minutes, treatment intervention using warm compress therapy and gout education. Post warm compress therapy (Tepid Water Sponge) Mr. S experienced different results, namely before applying a warm compress to gout sufferers with a pain scale of 6 (moderate pain) then after applying a warm compress it became a pain scale of 2 (mild pain) which was carried out for 7 meetings lasting 10-15 minutes. That while providing the warm compress technique (Tepid Water Sponge) was effective in reducing the pain felt by Mr. S thus experiencing a decrease of 4 levels.